Natural compounds may contribute in preventing SARS-CoV-2 infection: a narrative review - Maria Eleonora Bizzoca; Stefania Leuci; Michele Davide Mignogna; Eleonora Lo Muzio; Vito Carlo Alberto Caponio; Lorenzo Lo Muzio (Food Science and Human Wellness)
Coronavirus pandemic infection is the most important health issue worldwide. Coronavirus disease 2019 is a contagious disease characterized by severe acute respiratory syndrome coronavirus 2. To date, excluding the possibility of vaccination, against SARS-CoV-2 infection it is possible to act only with supportive care and non-virus-specific treatments in order to improve the patient's symptoms. Pharmaceutical industry is investigating effects of medicinal plants, phytochemical extracts and aromatic herbs to find out natural substances which may act as antiviral drugs. Several studies have revealed how these substances may interfere with the viral life cycle, viral entry, replication, assembly or discharge, as well as virus-specific host targets or stimulating the host immune system, reducing oxidative stress and inflammatory response. A natural compound can be used as a prophylaxis by people professionally exposed to the risk of contagion and/or positive patients not in intensive care. The aim of this paper is to perform a narrative review of current literature in order to summarize the most studied natural compounds and their modes of action.